2018
DOI: 10.1093/dote/doy025
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoabdominal pressure gradient and gastroesophageal reflux: insights from lung transplant candidates

Abstract: Advanced lung disease is associated with gastroesophageal reflux disease (GERD). The thoracoabdominal pressure gradient (TAPG) facilitates gastroesophageal reflux, but the effects of TAPG on gastroesophageal reflux in patients with pulmonary disease have not been well defined. Patients diagnosed with end-stage lung disease are expected to have the most extreme derangement in respiratory mechanics. The aim of this study is to explore the relationship between TAPG and reflux in lung transplant (LTx) candidates. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 17 publications
2
24
1
Order By: Relevance
“…These patients had higher DeMeester greater prevalence of pathological reflux, higher total time pH <4, and more total number of reflux episodes compared with patients who had adjusted thoracoabdominal pressure gradient ≤0 mmHg (15.2 vs. 6.3, P=0.006; 59.1 vs. 30.9%, P=0.022; 4.5 vs. 1.5%, P=0.003; 66.5 vs. 23.4, P=0.012, respectively). The study supported the claim that especially in patients with restrictive lung disease, that ventilator mechanics and an elevated adjusted thoracoabdominal pressure gradient play a role in the development of GERD (8).…”
Section: Gastroesophageal Reflux and Lung Diseasesupporting
confidence: 78%
See 1 more Smart Citation
“…These patients had higher DeMeester greater prevalence of pathological reflux, higher total time pH <4, and more total number of reflux episodes compared with patients who had adjusted thoracoabdominal pressure gradient ≤0 mmHg (15.2 vs. 6.3, P=0.006; 59.1 vs. 30.9%, P=0.022; 4.5 vs. 1.5%, P=0.003; 66.5 vs. 23.4, P=0.012, respectively). The study supported the claim that especially in patients with restrictive lung disease, that ventilator mechanics and an elevated adjusted thoracoabdominal pressure gradient play a role in the development of GERD (8).…”
Section: Gastroesophageal Reflux and Lung Diseasesupporting
confidence: 78%
“…The lung transplant population has a heterogeneous mix of etiologies, many with different risk factors for esophageal dysfunction as demonstrated in a number of studies (8,9). Connective tissue disease such as systemic sclerosis and scleroderma are commonly linked with pulmonary disease and can affect multiple systems including the gastrointestinal system.…”
Section: Esophageal Disease After Lung Transplantationmentioning
confidence: 99%
“…15 Intra-abdominal pressure (AP), intrathoracic pressure (TP), TAPG, and adjusted TAPG were measured during a resting period without swallowing or esophageal peristalsis (Figure 1), according to previously described methods. 16 Briefly, AP was defined as the pressure 1 cm below the lower border of the crural diaphragm at inspiration (referenced to atmospheric pressure), TP was defined as the pressure 5 cm above the upper border of the LES at inspiration (referenced to atmospheric pressure), and TAPG was calculated as AP minus TP. LESP, referenced to the pressure at the same level of AP measurement (1 cm below the lower border of the crus) was also assessed, and adjusted TAPG was calculated as TAPG minus pressure at the same level of AP measurement.…”
Section: High-resolution Manometrymentioning
confidence: 99%
“…Presumably, gastroesophageal reflux can be induced if TAPG overcomes LESP, which works as a fundamental barrier to reflux. 16,17 Manometric esophageal length between the lower border of the upper esophageal sphincter and the upper border of the LES at the end inspiration was assessed (Figure 1). The esophageal length index (ELI), which is the ratio of endoscopic esophageal length (centimeters) to patient height (meters), has been proposed by Yano and colleagues.…”
Section: High-resolution Manometrymentioning
confidence: 99%
“…The purpose of the EGDs was twofold: (1) to look for stigmata of GERD, and (2) for BE surveillance. We have recently shown that derangement of lung conditions affects the transdiaphragmatic pressure gradient, which can facilitate gastroesophageal reflux [5], and we therefore carry out full foregut examinations early in the post-LTx period. Surveillance endoscopies were performed annually in patients with nondysplastic BE, with fourquadrant biopsies at 1-cm intervals along the length of the involved segment of esophagus.…”
Section: Postoperative Esophagogastroduodenoscopymentioning
confidence: 99%